Realizing 21st Century Learning Through Inquirybased Learning: A Meta-Analysis - Army Trilidia Devega; Hilda Herasmus; Arina Luthfini Lubis; Ali Basriadi (Jurnal Penelitian Pendidikan IPA, 2025)
Throughout history, curiosity has driven individuals to explore and understand the essence of their existence. Inquiry-Based Learning (IBL) has emerged as a highly effective teaching method that empowers students to actively engage in the learning process, identify real-world problems, generate diverse solutions, and significantly enhance their learning experiences. This meta-analysis evaluates the effectiveness of IBL in fostering 21st-century skills such as critical thinking, problem-solving, and creativity. Using a systematic approach, sixteen articles from 2015 to 2024 were collected and analyzed through the PRISMA methodology, involving identification, screening, eligibility assessment, and inclusion. The sixteen primary studies meeting the inclusion criteria were analyzed using Hedge's random effects model. Results indicate that IBL significantly improves student outcomes, with an average effect size of 0.69, categorized as medium. Heterogeneity analysis showed significant variation among studies (Q = 47.849, p < 0.001). The Forest Plot demonstrated a statistically significant positive effect, while the Funnel Plot and Rosenthal's fail-safe N test indicated no publication bias, affirming the reliability of the results. IBL promotes active student participation through exploration, questioning, and real-world experiences, which are essential in 21st-century education. This meta-analysis underscores the substantial positive impact of IBL on student learning outcomes, suggesting its integration into curricula to enhance student skills in critical and creative thinking, thereby improving the quality of education globally. Theoretically, this study contributes to the pedagogical literature by providing empirical evidence for IBL's effectiveness across diverse educational contexts. Practically, the findings offer educators and policymakers evidence-based guidance for curriculum design and instructional strategies. The findings advocate for professional development and innovative teaching approaches to meet evolving educational needs